From Stone to Flesh: Transformation in Michel Henry’s Phenomenology of Life - Robert Farrugia (Aisthema: International Journal, 2022)
Michel Henry radicalizes subjectivity by removing all traces of objectivity and transcendence in order to secure its absolute immanence. He articulates this purification as a flight from the world towards life, which will be analysed here as a phenomenological transformation from stone to flesh. We will maintain that this interior conversion opens up a space between the man of the world and the Son of Life, as a passage from one state to the other that endures as a lived concrete experience. This analysis will serve to reappraise Henry’s non-intentional phenomenology of subjectivity, which he bases on a transcendental auto-affectivity that is prior to any intentional knowledge. Our intent is to inquire as to what extend is the latter mode of knowledge too late in order to elucidate its significant role within such a personal transformation.